2022
DOI: 10.1515/med-2022-0417
|View full text |Cite|
|
Sign up to set email alerts
|

circRNA_0001679/miR-338-3p/DUSP16 axis aggravates acute lung injury

Abstract: Acute lung injury (ALI) is a respiratory disorder characterized by acute respiratory failure. circRNA mus musculus (mmu)-circ_0001679 was reported overexpressed in septic mouse models of ALI. Here the function of circ_0001679 in sepsis-induced ALI was investigated. In vitro models and animal models with ALI were, respectively, established in mouse lung epithelial (MLE)-12 cells and C57BL/6 mice. Pulmonary specimens were harvested for examination of the pathological changes. The pulmonary permeability was exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 35 publications
1
10
0
Order By: Relevance
“…Luciferase reporter assay suggested that circRNA_0001679 positively regulated DUSP16 expression through sponging miR-338-3p. As a result, circRNA_0001679 indirectly induced cell apoptosis and upregulate the expression of proinflammatory cytokines, resulting in the aggravation of ALI [82]. This study provided valuable insight into circRNA_0001679's role in ALI and provided useful direction for further investigation of its therapeutic prospect in ALI.…”
Section: Acute Lung Injurymentioning
confidence: 79%
See 1 more Smart Citation
“…Luciferase reporter assay suggested that circRNA_0001679 positively regulated DUSP16 expression through sponging miR-338-3p. As a result, circRNA_0001679 indirectly induced cell apoptosis and upregulate the expression of proinflammatory cytokines, resulting in the aggravation of ALI [82]. This study provided valuable insight into circRNA_0001679's role in ALI and provided useful direction for further investigation of its therapeutic prospect in ALI.…”
Section: Acute Lung Injurymentioning
confidence: 79%
“…Promotes fibroblast proliferation and lung fibroblast-to-myofibroblast transition [68] hsa_circ_0058493 upregulated Potential biomarker candiate [69] Silicosis circZC3H4 upregulated Regulates fibroblast activation and proliferation [71] Cigarette particle-induced lung injury circFOXO3 upregulated Promotes inflammatory response [74] circRNA_0006892 downregulated Promotes cell apoptosis and inflammatory response [75] Pulmonary hypertension circRNA_004592 upregulated Promotes cell proliferation and inhibits cell apoptosis [79] Acute lung injury hsa_circ_0059930 upregulated Inhibits cell apoptosis and inhibits cell proliferation [81] circRNA_0001679 upregulated Promotes cell apoptosis and proinflammatory cytokines [82] circHECTD1 downregulated Inhibits cell apoptosis [83] Kidney Mesangial cell Injury circLRP6 upregulated Promotes inflammatory response [33] Acute kidney injury circ_0114428 upregulated Promotes inflammatory response [90] circFANCA upregulated Promotes cell apoptosis, inflammatory response, oxidative stress [91] circ_RASGEF1B upregulated Promotes cell apoptosis and inflammatory response [92] circ_BNIP3L upregulated Promotes inflammatory response and oxidative stress [93] circ_0114427 upregulated Promotes inflammatory response [94] circSnrk upregulated Promotes cell apoptosis [27] hsa_circ_010157 upregulated Promotes cell apoptosis and inflammatory response [95] circTLK1 upregulated Promotes cell apoptosis, inflammatory response, oxidative stress [96] circHIPK3 upregulated Promotes cell apoptosis and inflammatory response from circRNAs derived from the extracellular exosomes of TBI-induced mouse brain. The study suggested that the extracellular circRNAs in brain-derived exosomes could involve in dendrite development and glutamatergic synapse formation [48].…”
Section: Lung Idiopathic Pulomnary Fibrosis Circhipk3 Upregulatedmentioning
confidence: 99%
“…In vivo and in vitro experiments have demonstrated the potential therapeutic targets in SAOD; for instance, Xie et al (33) revealed that NORAD knockdown alleviates kidney injury in mice and decreases the inflammatory response and apoptosis of LPS-stimulated HK-2 cells via the miR-577/GOLPH3 axis. In another study, DUSP16 overexpression reverses the effect of circ_0001679 knockdown in LPS-stimulated lung epithelial-12 cells; furthermore, circ_0001679 knockdown attenuates lung pathological changes, reduces pulmonary microvascular permeability, and suppresses inflammation in ALI mice (34).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, circRNAs can regulate a variety of molecular mechanisms, including inflammation and immune responses, as well as a variety of biological processes in various metabolic organs 11 . For example, altering circ-fatty acid desaturase 2 or circ_0001679 at the gene level can inhibit sepsis-induced ALI progression 6,12 . CircRNA protein tyrosine kinase 2 (circPTK2) has attracted academic attention in the aspect of malignancy [13][14][15] and has also been studied to mediate Circular RNA protein tyrosine kinase 2 aggravates pyroptosis and inflammation in septic lung tissue by promoting microRNA-766/ eukaryotic initiation factor 5A axis-mediated ATP efflux apoptosis and inflammatory response in sepsis-induced myocardial injury 16 .…”
Section: Introductionmentioning
confidence: 99%
“…Notably, circPTK2 can also regulate sepsis-induced microglial activation and apoptosis in the hippocampus 17 . Since circRNAs absorb miRNA to upregulate target genes by isolating and competitively inhibiting miRNA activity 9,12 , this study intended to explore whether circPTK2 mediates septic ALI in this way.…”
Section: Introductionmentioning
confidence: 99%